Effects of Intensity and Set Method on iEMG of Flexor Carpi Ulnaris and Performance Speed Decrease Point during Barbell Curl Exercise (Medico Legal Update, 2019)
The purpose of this study was to investigate the effects of repetition time changes during barbell curl exerciseon EMG responses.In this study, the subjects were selected from twelve men in their twenties who had morethan 3 years of resistance exercise experience. In this case, the subjects were randomly assigned to threeconditions at intervals of one week with different rest interval and intensity (50%1RM/1min, 70%1RM/2min,90%1RM/3min). When each condition was performed, each one repetition time and iEMG of the agonistwere measured and reviewed. In each instance, a statistical analysis was performed by repeated measuresof two-way ANOVA, with a p value=.05. In the review of the results of this study, iEMG of flexor carpiulnaris during the performance of the barbell curl movement increased significantly with the occurrence ofperformance speed decrease point in all intensity,. and was significantly noted with the progression of the setonly at 50%1RM and 70%1RM. The point of occurrence of repetition speed decrease point was significantlydifferent according to exercise intensity. Generally speaking, the heavier the weight, the closer was thepoint of performance speed decrease point and the end of exercise. To that end, the point of occurrence ofperformance speed decrease point according to the set also showed a significant difference. In this case, asthe set progressed, there was a tendency that the point of performance speed decrease point was close tothe point of stopping motion. There In conclusion, it is important to consider the fatigue facstor associatedwith decreased performance during resistance exercise, and the important role of a supporter should beconsidered and utilized when exercise speed is decreased as an exercise set progresses during a regimen.